TESTING ACCURACY OF BUTT LOG VOLUME ESTIMATED BY USING SEVEN FORMULAS FOR CALIBRAIN PINE ( Pinus brutia Ten ) - Mohammed Obeyed (Mesopotamia Journal of Agriculture, 2019)
The observed volumes obtained by several volume calculation methods for the butt log volume of Calibrain pine (Pinus brutia Ten.). These butt logs were compared with true volume of each butt log which was determined by aggregating the volumes of measured short (1m) using Smalian’s formula. 150 of sample trees were measured into Zaweta and Atrush districts of Dohuk province. The sample trees presented diameter at breast height from 13.9 to 37.6 cm. and total height from 8 - 19.2 meter.The volume of each butt log was estimated by using (Smalian’s, Huber’s, Newton’s, Hossfeld’s, Bruce’s, Sorenson’s and Centroid method). The accuracy of these seven procedures was analyzed considering volume of butt log lengths 6-m. The results showed that Centroid method was superior for all volumes. As expected, Sorenson formula was the procedure with the worst performance.  <span style="mso-ascii-font-family: 'Times New Roman'; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: 'Times New Roman'; mso-hansi-font-family: 'Times New Roman'; mso-hansi-theme-font: major-bidi; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: major-bidi;">TESTING ACCURACY OF BUTT LOG VOLUME ESTIMATED BY USING SEVEN FORMULAS FOR CALIBRAIN PINE ( Pinus brutia Ten )